PANCHAKARMA AND SHAMAN CHIKITSA IN TRIGGER FINGER - Prajakta A. Pashte,; V. J. Tiwari, (International Journal of Ayurveda and Pharma Research, 2020)
Leech therapy is proven to be having marvelous effect in various types of diseases which includes Raktadushti. Trigger finger is a disease usually occurring in patients having repeated finger movements. It causes one or more finger to get stuck in curled up position which requires manual help for straightening it up. If not cured patient has to undergo surgery which has its own disadvantages. Jalaukavcharana which is one among the Panchashodhana along with Basti Chikitsa proven to get significant result in patient suffering from condition for 6 months span. Acharya Charak has mentioned in Vatarakta Chikitsa, Raktamokshana is the half treatment of Raktadushtikara Vyadhis. In Vatapradhan Vaatrakta, Acharya Charaka has mentioned Anguli Sandhi Sankoch, Akunchana which is similar to symptoms of trigger finger. Here, Kandara being Upadhatu of Rakta can be considered as Rakta Dushti as well as Vata Dushti, where Vatanulomana and Rakta Shodhana is required. In this study a case of trigger finger was treated with Jalaukavcharana for 3 sittings at the interval of 7 days along with Basti Chikitsa and Avgaha Sweda of b/l hands for 7 days, which showed the relief in symptoms within 14 days span. Observation and results were drawn on the basis of assessment criteria. Discussion was done on the basis of entire observations during research. Conclusion was drawn on the basis of result.